TV Dizileri Yoluyla Yeniden Üretilen Tüketim Kültürü / The Re-produced Consumption Culture by TV Series - Kula, Nesrin (Journal of History Culture and Art Research, 2013)
Tüketme terimi tahrip etmek, harcamak, israf etmek, bitirmek anlamlarını taşımaktadır. Jean Baudrillard ise, tüketimi kodlar ve kurallarla düzenlenmiş bir göstergeler sistemi olarak tanımlamaktadır. Tüketim tarzları kişilerin kimliklerinin birer unsuru haline gelmektedir. Özneler kimliklerini ifade etmek amacıyla metaları kullanmakta ve kişilerin toplum içindeki statüsü tükettikleri ile ölçülür hale gelmektedir. TV dizileri de, bireylere tüketilecek sonsuz nesneler yoluyla oluşturulacak yaşam tarzları ile ilgili bilgiler vermektedir. Çalışmada, seçilen on dizide üretilen anlam dünyası, yeniden üretilen tüketim ideolojisi ve oluşturulan kadın ve erkek rol modelleri çözümlenmektir. The Re-produced Consumption Culture by TV Series The concept of consumption means ’to destroy, spend, waste or finish something’. Jean Baudrillard describes the consumption as a semiotic system regulated of codes and rules. Consumption styles are nowadays becoming an element of people’s identity. Individuals use the commodities to express their identities and therefore the status of people in the community being measured according to what they consume. Meanwhile many TV series provides information to individuals about lifestyles to be created by infinite items consumed. This study analyzes the mindset created in ten selected TV series and the re-produced ideology of consumption as well as the presented role models for women and men in them.